Concrete anti-cracking self-repairing agent and preparation method thereof

By using the synergistic effect of ZSM-5 zeolite molecular sieve loaded with Bacillus pasteurianus spores and Fe3O4@SiO2 core-shell nanoparticles in concrete, the problems of difficulty in maintaining microbial activity and insufficient calcium ion supply efficiency were solved, and rapid and effective repair of concrete cracks was achieved.

CN120757324APending Publication Date: 2025-10-10GUANGZHOU CITY CONSTR COLLEGE

Patent Information

Application Number
CN202510933975.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-08
Publication Date
2025-10-10

AI Technical Summary

Technical Problem

In existing concrete self-repair technologies, microbial activity is difficult to maintain, calcium ion supply efficiency is insufficient, and the corresponding repair depth and speed are limited, resulting in deficiencies in the long-term stability and repair efficiency of the self-repair system.

Method used

ZSM-5 zeolite molecular sieve is used to load Bacillus pasteurianus spores, combined with Fe3O4@SiO2 core-shell nanoparticles and PLGA microspheres to form a magnetothermal responsive capsule layer. Through the synergistic effect of mesoporous silica particles and directional mineralization promoters, accurate identification, activation and continuous energy supply of cracks are achieved.

Benefits of technology

It significantly prolongs the spore survival cycle, shortens the repair cycle, improves the efficiency of calcium ion supply, achieves rapid and effective repair of cracks, and forms a full-chain collaborative repair mechanism, which is suitable for autonomous repair of multiple types of damage.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a concrete anti-cracking self-repairing agent in the technical field of building materials, and aims to solve the problem that concrete cracks are difficult to self-repair. According to the technical scheme, the self-repairing agent is characterized by comprising a microbial repairing unit formed by ZSM-5 type zeolite molecular sieve loaded bacillus pasteurii spores, mesoporous silica particles loaded with L-calcium aspartate and Fe3O4 (at) SiO2 core-shell nanoparticles which are fixed through an in-situ polymerization coating layer to form a magnetic thermal response capsule layer coating the surface of the microbial repairing unit, pLGA microspheres containing yeast extract are positioned on an interface of zeolite and hydrogel, and a trehalose-anhydrous calcium chloride eutectic compound is used as a directional mineralization accelerant. The concrete anti-cracking self-repairing agent provided by the invention is mainly used for intelligent identification and self-repairing of concrete cracks, and efficient repairing is realized through a microbial mineralization, calcium ion slow release and magnetic thermal response synergistic mechanism.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of building materials, and more particularly to a concrete anti-cracking self-repairing agent and a preparation method thereof. Background Art

[0002] Autonomous repair technology for concrete cracks faces several technical bottlenecks. Microbial mineralization repair methods are susceptible to inactivation in highly alkaline concrete environments (pH > 12), making conventional carriers ineffective in providing long-term, effective protection. Furthermore, the lack of a precise activation mechanism during the initial crack formation phase prevents microorganisms from promptly initiating the repair process in the target area. This problem stems from the inherently strong alkalinity of cement hydration reactions, and developing carriers with both ion isolation and biocompatibility presents technical challenges.

[0003] The calcium ion supply system suffers from efficiency deficiencies. Traditional inorganic calcium sources easily react with hydroxide ions and precipitate during the concrete mixing stage, resulting in premature consumption. Organic calcium sources, on the other hand, diffuse and are lost due to pore water migration, making it difficult to maintain an effective concentration in cracked areas. The uncontrolled release of calcium ions results in a lack of continuous raw material supply for the microbial mineralization process, primarily influenced by the dynamic movement of fluid within the porous concrete medium. Existing coating technologies make it difficult to achieve crack-specific release.

[0004] The depth and speed of the repair response are significantly limited. Microbial mineralization requires a multi-stage process of spore germination, metabolism, and mineralization, resulting in a long repair cycle. Due to size effects, microcracks (<0.2mm) are difficult for repair components to penetrate. Existing technologies rely on passive diffusion mechanisms and lack active driving means to accelerate the repair process. The application of external energy fields (such as magnetic fields) is difficult to effectively transmit to internal repair units due to the shielding effect of concrete on electromagnetic waves, and the thermal effect may damage the concrete matrix material.

[0005] The root cause of the above technical bottlenecks lies in the constraints of the physical and chemical properties of the concrete material itself, as well as the complexity of the interaction between the repair system and the matrix, which leads to deficiencies in the long-term stability and repair efficiency of the existing self-repair system. Summary of the Invention

[0006] An object of the present invention is to solve at least the above problems and to provide at least the advantages which will be described hereinafter.

[0007] Another object of the present invention is to provide a concrete anti-cracking self-repairing agent and a preparation method thereof, which solves the technical problems in the prior art of difficulty in maintaining microbial activity, insufficient calcium ion supply efficiency, and limited corresponding repair depth and speed.

[0008] To achieve these objectives and other advantages according to the present invention, a concrete anti-cracking self-repairing agent is provided, characterized in that it comprises the following raw materials in parts by weight: 100 parts of ZSM-5 zeolite molecular sieve, 5-8 parts of Bacillus pasteurianus spores, 10-15 parts of mesoporous silica particles loaded with calcium L-aspartate with a particle size of 100-200 nm, 10-15 parts of Fe3O4@SiO2 core-shell nanoparticles, 8-12 parts of PLGA microspheres, and 3-5 parts of a directional mineralization promoter; Among them, Bacillus pasteurianus spores are loaded in the nanochannels of ZSM-5 zeolite molecular sieve to form a microbial remediation unit. The molar ratio of SiO2 and Al2O3 of ZSM-5 zeolite molecular sieve is 30-50:1, and the pore size is ≥0.8nm; Fe3O4@SiO2 core-shell nanoparticles are fixed by in-situ polymerization coating to form a magnetothermal responsive capsule layer coated on the surface of the microbial remediation unit; the particle size of Fe3O4@SiO2 core-shell nanoparticles is 50-100nm, and the shell thickness is 5-10nm; The PLGA microspheres contain yeast extract, and the PLGA microspheres are located at the interface between the zeolite carrier and the coating layer; The directional mineralization promoter is a eutectic complex formed by trehalose and anhydrous calcium chloride.

[0009] Preferably, in the concrete anti-cracking self-repairing agent, polyethyleneimine is bonded to the surface of the mesoporous silica particle carrier, and poly-γ-glutamic acid is adsorbed through electrostatic action to form a double-layer slow-release barrier coated with calcium L-aspartate.

[0010] Preferably, the concrete anti-cracking self-repairing agent comprises a carbon nanotube network in the nanochannels of the ZSM-5 zeolite molecular sieve loaded with Bacillus pasteurianus spores; The carbon nanotubes are carboxylated single-walled carbon nanotubes with a diameter of 1-2nm, a length of 200-500nm, and a surface grafting density of 3-5 per 100nm. 2 The carbon nanotube network occupies 10-15% of the volume of the zeolite channel, and its two ends connect the spore surface to the inner wall of the zeolite channel.

[0011] Preferably, the preparation method of the concrete anti-cracking self-repairing agent and directional mineralization accelerator is as follows: S11, dissolving a nanocellulose whisker framework whose surface is modified with 3-aminopropyltriethoxysilane, trehalose, and anhydrous calcium chloride in deionized water, and stirring at 60-70° C. to form a homogeneous solution; wherein the molar ratio of trehalose to anhydrous calcium chloride is 1:1.5-2.0, and the amount of the nanocellulose whisker framework added is 0.5-1.5% of the total mass of trehalose and anhydrous calcium chloride; S12, cooling the homogeneous solution of step S11 to -40 to -30°C at a rate of 5-10°C / min, keeping the temperature and freezing for 2-3 hours to obtain a frozen body; S13, placing the frozen body obtained in step S12 in a freeze dryer with a vacuum degree of ≤10 Pa, and subliming and dehydrating at -50 to -45°C for 24-36 hours to obtain a freeze-dried solid; S14. The freeze-dried solid obtained in step S13 is subjected to ball milling at a speed of 400-600 rpm for 20-30 minutes under an inert atmosphere, and sieved to obtain eutectic composite particles with a particle size of 10-50 μm.

[0012] Preferably, the surface of the concrete anti-cracking self-repairing agent and the directional mineralization promoter is coated with a magnetic responsive shell, which includes an electrostatic adsorption layer, a magnetic carrier layer and an encapsulation layer from the inside to the outside; the electrostatic adsorption layer is a positively charged polyethyleneimine polymer with a thickness of 2-5nm; the magnetic carrier layer is amino-ferric oxide nanoparticles with a particle size of 10-20nm, which are fixed on the electrostatic adsorption layer by electrostatic action; the encapsulation layer is a hydrophobic silica vapor deposition film with a thickness of 3-8nm.

[0013] Preferably, the preparation method of the concrete anti-cracking self-repairing agent and the directional mineralization accelerator with the surface coated with a magnetic responsive shell is as follows: S21, dispersing the directional mineralization promoter particles in a buffer solution of pH 5.0-6.0, adding a positively charged polyethyleneimine polymer, and stirring the mixture for 30-60 minutes to form an electrostatic adsorption layer with a thickness of 2-5 nm; S22, adding amino-ferroferric oxide nanoparticles with a particle size of 10-20 nm to the system of step S21, and ultrasonically treating at 25-35° C. for 20-40 minutes to fix the magnetic particles to the surface of the electrostatic adsorption layer through electrostatic action to form a magnetic carrier layer, thereby obtaining composite particles; S23, placing the composite particles in step S22 in a vapor deposition reaction chamber, introducing hexamethyldisilazane vapor, and reacting at 150-200° C. and 0.1-0.5 Pa pressure for 1-2 hours to form a hydrophobic silicon dioxide encapsulation layer with a thickness of 3-8 nm.

[0014] Preferably, the concrete anti-cracking self-repairing agent has a gradient transition layer on the surface of the magnetothermal response capsule layer, which includes, from the inside to the outside, a first bonding layer, a second cross-linking layer and a third permeation layer; the first bonding layer is a polydopamine coating with a thickness of 5-10 nm, which is coated on the surface of the magnetothermal response capsule layer; the second cross-linking layer is a copolymer network of polyethylene glycol diacrylate and zinc acrylate, with a network pore diameter of 30-50 nm; the third permeation layer is a cage-type polysilsesquioxane nanoparticle with a surface modified epoxy group, with a particle size of 20-40 nm, which is dispersed in the second cross-linking layer network.

[0015] The present invention also provides a method for preparing a concrete anti-cracking self-repairing agent, which comprises the following steps: Step 1: Disperse Bacillus pasteurianus spores in phosphate buffer, add ZSM-5 zeolite molecular sieve, and oscillate and infiltrate at a vacuum degree of 0.08-0.1 MPa and a temperature of 25-30°C for 30-60 minutes to obtain a microbial remediation unit; Step 2: mixing Fe3O4@SiO2 core-shell nanoparticles with a precursor solution containing 2-hydroxyethyl acrylate, glycidyl methacrylate, and photoinitiator Irgacure 2959 to obtain a mixture; Step 3: Apply the mixture obtained in step 2 to the surface of the microbial remediation unit obtained in step 1 to form a coating system, and perform the following treatments on the coating system in sequence: S31, adding 0.5-1% by mass of dopamine hydrochloride to the coating system, and standing at pH 8.5-9.0 for 1-2 hours under nitrogen protection to form a first polydopamine binding layer; S32, adding polyethylene glycol diacrylate with a molecular weight of 200-400Da and zinc acrylate in a molar ratio of 3:1, under the UV intensity of 10-15mW / cm 2 Irradiate for 5-10 minutes to initiate free radical polymerization to form a second cross-linked layer; S33, finally adding 2-5% of the mixture by mass of surface-modified epoxy group-containing cage-type polysilsesquioxane nanoparticles, and continuing irradiation for 2-3 minutes to form a third permeation layer and a magnetothermal responsive capsule layer; Step 4: adding the mesoporous silica particles, PLGA microspheres, and directional mineralization promoter to the product of step 3, and mixing at a shear rate of 200-400 rpm and a temperature of 15-20° C. for 20-30 minutes to obtain a composite; Step 5: Place the compound obtained in step 4 in a mold, and allow it to stand and cure for 48-72 hours in an environment with a humidity of ≥90% and a temperature of 35-40° C. to obtain a concrete anti-cracking self-repairing agent.

[0016] The present invention has at least the following beneficial effects: 1. The present invention achieves a systematic improvement in crack repair efficiency through the synergistic functions of multiple components: the nanochannel confinement effect of the zeolite molecular sieve (pore size ≥ 0.8 nm, SiO2 / Al2O3 molar ratio 30-50:1) creates a physical barrier to prevent OH⁻ corrosion in the concrete pore fluid, significantly extending the spore survival period; the mesoporous silica-loaded L-aspartate calcium forms an enzyme-responsive calcium source, whose release kinetics are autonomously regulated by microbial metabolic activity, avoiding early alkaline consumption and ineffective diffusion; the magnetothermal responsive capsule layer (Fe3O4@SiO2 core-shell structure) converts external alternating magnetic field energy into a localized thermal effect (40-50°C), simultaneously accelerating the spore germination rate and enhancing the diffusion coefficient of the repair component in microcracks; the precise positioning of PLGA microspheres at the zeolite-hydrogel interface provides continuous nutrient release, matching the metabolic needs of the microbial mineralization process; and the trehalose-calcium chloride eutectic complex promotes the directional growth of calcite nuclei along the crack walls by reducing the crystallization activation energy. The functional complementarity of each component is designed based on the environmental characteristics of concrete (high alkalinity, pore fluid migration, and crack scale gradient), realizing a full-chain synergistic repair mechanism of "identification-activation-energy supply-mineralization-enhancement"; 2. The preparation method provided by the present invention ensures the precise construction of functional structure and the integrity of biological activity by controlling key parameters. The vacuum infiltration stage (0.08-0.1MPa, 25-30℃) maintains the balance between the osmotic pressure of the buffer and the intracellular pressure of the spores to avoid mechanical damage; the photopolymerization process adopts low-intensity ultraviolet irradiation (10-15mW / cm 2 ) and short operation time (5-10min), controlling the reaction exotherm below the microbial heat resistance threshold (40℃); the gradient transition layer is constructed in sequence (polydopamine → cross-linked network → permeable particles) to establish a three-level interface strengthening mechanism - the catechol group of polydopamine strongly chelates with the Fe3O4@SiO2 surface to enhance the binding energy, and the polyethylene glycol diacrylate / zinc acrylate copolymer network is connected through Zn 2+ -Carboxyl coordination buffers expansion stress differences, and the epoxy ring-opening reaction of cage-type polysilsesquioxane forms 30-50nm through-channels to enhance deep penetration; low-temperature vapor deposition (150-200℃) of a directional mineralization promoter and an integrated freeze-drying-ball milling process achieves uniform coating of the magnetically responsive shell while maintaining the integrity of the eutectic structure; this method systematically avoids the risks of bioactivity damage, interlayer delamination, and functional inactivation in traditional processes.

[0017] Other advantages, objectives and features of the present invention will be reflected in part from the following description and will be understood by those skilled in the art through study and practice of the present invention. DETAILED DESCRIPTION

[0018] The present invention is further described in detail below with reference to the embodiments so that those skilled in the art can implement the invention with reference to the description.

[0019] It should be understood that terms such as “having”, “including” and “comprising” used herein do not preclude the existence or addition of one or more other elements or combinations thereof.

[0020] It should be noted that the experimental methods described in the following embodiments are conventional methods unless otherwise specified, and the reagents and materials can be obtained from commercial channels unless otherwise specified.

[0021] The present invention provides a concrete anti-cracking self-repairing agent, which comprises the following raw materials in parts by weight: 100 parts of ZSM-5 zeolite molecular sieve, 5-8 parts of Bacillus pasteurianus spores, 10-15 parts of mesoporous silica particles loaded with calcium L-aspartate with a particle size of 100-200 nm, 10-15 parts of Fe3O4@SiO2 core-shell nanoparticles, 8-12 parts of PLGA microspheres, and 3-5 parts of a directional mineralization accelerator; Among them, Bacillus pasteurianus spores are loaded in the nanochannels of ZSM-5 zeolite molecular sieve to form a microbial remediation unit. The molar ratio of SiO2 and Al2O3 of ZSM-5 zeolite molecular sieve is 30-50:1, and the pore size is ≥0.8nm; Fe3O4@SiO2 core-shell nanoparticles are fixed by in-situ polymerization coating to form a magnetothermal responsive capsule layer coated on the surface of the microbial remediation unit; the particle size of Fe3O4@SiO2 core-shell nanoparticles is 50-100nm, and the shell thickness is 5-10nm; The PLGA microspheres contain yeast extract, and the PLGA microspheres are located at the interface between the zeolite carrier and the coating layer; The directional mineralization promoter is a eutectic complex formed by trehalose and anhydrous calcium chloride.

[0022] In the above technical solution, the microbial remediation unit is a ZSM-5 zeolite molecular sieve loaded with Bacillus pasteurianus spores. Its pore size ≥0.8 nm provides a physical confinement barrier, and a SiO2 / Al2O3 molar ratio of 30-50:1 regulates ion permeability. The magnetothermal responsive capsule layer is fabricated as follows: Fe3O4@SiO2 core-shell nanoparticles (core 50-100 nm, shell 5-10 nm) are dispersed in a prefabricated pH-sensitive hydrogel precursor solution. After UV irradiation, the pH-sensitive hydrogel is formed through in situ photocrosslinking. The Fe3O4@SiO2 core-shell nanoparticles are then dispersed in the in situ generated pH-sensitive hydrogel and fixed with an in situ polymerized coating to form a magnetothermal responsive capsule layer coated on the surface of the microbial remediation unit. External energy is converted through the magnetothermal effect. The directional mineralization promoter is a eutectic complex of trehalose and anhydrous calcium chloride, which promotes calcium carbonate deposition by lowering the crystallization energy barrier. The precursor solution of the pH-sensitive hydrogel consists of 15 parts of 2-hydroxyethyl acrylate, 10 parts of glycidyl methacrylate, and 0.25 parts of photoinitiator Irgacure 2959. The carboxyl groups are protonated and dissolved in an acidic environment, and 2-hydroxyethyl acrylate and 10 parts of glycidyl methacrylate copolymerize to form a cross-linked copolymer.

[0023] In the above technical solution, the preparation process first disperses Bacillus pasteurianus spores in phosphate buffer, adds ZSM-5 zeolite molecular sieve, and oscillates and infiltrates at a vacuum of 0.08-0.1MPa and 25-30°C to allow the spores to enter the nanochannels. Subsequently, Fe3O4@SiO2 core-shell nanoparticles are mixed with a precursor solution containing 2-hydroxyethyl acrylate, glycidyl methacrylate, and a photoinitiator, and coated on the surface of the zeolite carrier. The coating system is treated with dopamine hydrochloride to form a polydopamine binding layer, and then polyethylene glycol diacrylate and zinc acrylate are introduced for UV cross-linking to construct a network layer. Finally, epoxy cage-type polysilsesquioxane nanoparticles are incorporated to form a permeation layer. After shear mixing, the PLGA microspheres and directional mineralization promoter are cured and formed in an environment with a humidity of ≥90% and a temperature of 35-40°C.

[0024] Conventional microbial self-healing agents use diatomaceous earth or bentonite as carriers, which have a wide pore size distribution (1-50μm) and are unable to block OH⁻ ion penetration, resulting in spore inactivation within 72 hours in highly alkaline environments. However, the uniform nanochannels (pore size ≥0.8nm) of the zeolite molecular sieve in this solution can extend the spore survival period to 28 days. Existing calcium sources are often directly added with calcium lactate or calcium carbonate, which reacts with OH⁻ during the concrete mixing stage and precipitates, resulting in calcium utilization rates below 30%. The mesoporous silica-loaded calcium L-aspartate in this solution uses an enzyme-responsive release mechanism to target calcium ions after cracks appear, increasing utilization to over 80%. Traditional repair systems rely on passive diffusion, requiring 14-28 days to repair microcracks. The magnetothermal responsive capsule layer in this solution generates a localized thermal effect under an alternating magnetic field, shortening spore germination time by 50% and shortening the repair cycle to 3-7 days.

[0025] The above technical solution achieves triple synergistic effects: the nano-confinement effect of the zeolite carrier blocks alkaline corrosion and maintains the long-term dormancy stability of spores; the reduction of pH at the crack triggers the dissolution of the hydrogel, precisely activating microbial metabolism; the magnetothermal effect simultaneously accelerates calcium ion migration and mineralization deposition. The slow-release properties of mesoporous silica avoid premature consumption of the calcium source, and the eutectic complex promotes the directional growth of calcite along the crack wall. Ultimately, a closed-loop self-repair system is formed from crack identification, component activation to mineralization repair, which is suitable for the self-repair of various types of damage such as concrete shrinkage cracks and load cracks. In another technical solution, the concrete anti-cracking self-repairing agent has polyethyleneimine bonded to the surface of the mesoporous silica particle carrier, and adsorbs poly-γ-glutamic acid through electrostatic action to form a double-layer slow-release barrier coated with L-aspartic acid calcium.

[0026] In the above technical solution, mesoporous silica particles refer to porous silica carriers with pore sizes of 2-5 nm and particle sizes of 100-200 nm. Their surfaces are modified with a silane coupling agent and bonded with long polyethyleneimine (PEI) chains. Calcium L-aspartate is an organic calcium compound with a molecular size of approximately 1.2 nm. Poly-gamma-glutamic acid (PGA) is an anionic biopolymer that electrostatically adsorbs onto the PEI layer to form a coating. The double-layer sustained-release barrier, consisting of an inner covalently bonded PEI layer and an outer electrostatically adsorbed PGA layer, delays calcium ion release through steric hindrance and charge repulsion.

[0027] In this technical solution, mesoporous silica is first dispersed in anhydrous ethanol. 3-Aminopropyltriethoxysilane (APTES) is then added and refluxed at 70°C for 4 hours to form surface amino groups. After centrifugal washing, the modified particles are immersed in a 5wt% calcium L-aspartate solution and loaded with a calcium source by vacuum infiltration. Subsequently, a 0.1wt% PEI solution is added to a pH 9.0 boric acid buffer solution and stirred for 30 minutes to form an inner polymer membrane. Finally, the particles are transferred to a sodium acetate buffer (pH 5.0) containing 1wt% PGA (molecular weight 200 kDa) and electrostatically self-assembled for 1 hour to form an outer barrier layer. The product is freeze-dried to obtain calcium-loaded composite particles.

[0028] Conventional single-layer coating technology uses a single polymer (such as chitosan) to directly encapsulate the calcium source. This polymer is susceptible to ion exchange dissociation in the high calcium ion environment (>20mM) of the concrete pore fluid, causing the coating to rupture and fail within 48 hours. In this solution's double-layer structure, the inner PEI layer is firmly bonded to the carrier surface via covalent bonds, resisting ion impact. The outer PGA layer's electrostatic interaction with PEI provides dynamic self-healing properties. When the coating is partially damaged, the free PGA in the solution can immediately fill the gap and repair it. The existing technology has a burst release rate of calcium ions (>60% in the first hour), resulting in ineffective early release. However, this double-layer barrier reduces the burst release rate to below 20%, maintaining an effective calcium concentration in the crack area for up to 14 days.

[0029] This technical solution achieves precise control of the kinetics of calcium ion release: the PEI layer forms a primary barrier through the coordination of amino groups with calcium ions, while the PGA layer relies on a network of carboxyl anions to establish a secondary diffusion barrier. In the early stages of crack formation, proteases secreted by microorganisms specifically degrade the PGA layer, initiating the slow release of calcium ions. As the crack expands, the PEI layer gradually dissolves and releases residual calcium sources. This phased release characteristic matches the calcium demand of the crack at different stages of development, avoiding the drawbacks of traditional technologies, characterized by "excessive release in the early stages and insufficient supply in the later stages." The double-layer barrier significantly improves its stability in the high-alkaline environment of concrete, ensuring the continued effectiveness of the repair agent throughout its service life.

[0030] In another technical solution, the concrete anti-cracking self-repairing agent comprises a carbon nanotube network in the nanochannels of the ZSM-5 zeolite molecular sieve loaded with Bacillus pasteurianus spores; The carbon nanotubes are carboxylated single-walled carbon nanotubes with a diameter of 1-2nm, a length of 200-500nm, and a surface grafting density of 3-5 per 100nm. 2 The carbon nanotube network occupies 10-15% of the volume of the zeolite channel, and its two ends connect the spore surface to the inner wall of the zeolite channel.

[0031] In the above technical solution, carboxylated single-walled carbon nanotubes refer to one-dimensional nanomaterials with a diameter of 1-2nm and a length of 200-500nm, with carboxyl functional groups (-COOH) modified on the surface. The carbon nanotube network refers to a three-dimensional conductive structure that connects spore surface proteins with the silanol groups on the inner wall of the zeolite channel through amide bonds, with a grafting density of 100nm per 100nm. 2 There are 3-5 connection points on the surface. The zeolite channel volume ratio refers to the carbon tube network occupying 10-15% of the zeolite channel space, leaving enough space for spore metabolism.

[0032] In this technical solution, ZSM-5 zeolite is immersed in an N-hydroxysuccinimide (NHS) activation solution containing 1 wt% carbon nanotubes. Ultrasonic dispersion is then performed for 30 minutes to allow the carbon nanotubes to enter the pores. 1-Ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC) catalyst is then added, and the mixture reacts in a pH 6.0 buffer for 2 hours, allowing the carbon nanotube carboxyl groups to condense with the silanol groups on the zeolite surface to form ester bonds. A suspension of Bacillus pasteurianus spores is then injected, and under vacuum agitation, the spores enter the pores. The residual carboxyl groups on the carbon nanotube surface connect with the amino groups on the spore coat protein through an amidation reaction, ultimately forming a continuous anchoring structure: zeolite inner wall, carbon nanotube network, and spore surface.

[0033] In traditional physical adsorption loading technology, spores only rely on van der Waals forces to adhere to the carrier surface. -1 ) in a nutrient carrier, over 60% of the spores detached from the carrier. The carbon nanotube network in this scheme achieves multi-point anchoring through chemical bonding: ester bonds to the zeolite (bond energy ~340kJ / mol) resist shear stress; amide bonds to the spores (bond energy ~300kJ / mol) prevent interfacial slip. Existing carriers rely on concentration gradients for nutrient diffusion, requiring yeast extract to migrate to the spores over a distance >5μm. In this scheme, the hollow channels of the carbon nanotubes (inner diameter >0.8nm) form a molecular-scale transport path, shortening the diffusion distance to the carbon nanotube length scale (200-500nm), and increasing nutrient transport efficiency by more than threefold.

[0034] This technical solution establishes a stable biofilm-carrier interface system: the spatial confinement of the carbon nanotube network inhibits spore displacement caused by concrete stress transmission, ensuring spore survival. The capillary action of its nanochannels directs the delivery of yeast extract permeated through the hydrogel layer, shortening the nutrient diffusion path. The conductive network also simultaneously transfers electrons generated by microbial metabolism, maintaining intracellular redox balance. Ultimately, this achieves a synergistic optimization of the carrier's protective efficacy and metabolic activity, overcoming the bottleneck inherent in conventional technologies where enhanced protection leads to suppressed metabolism.

[0035] In another technical solution, the preparation method of the concrete anti-cracking self-repairing agent and directional mineralization accelerator is specifically as follows: S11, dissolving a nanocellulose whisker framework whose surface is modified with 3-aminopropyltriethoxysilane, trehalose, and anhydrous calcium chloride in deionized water, and stirring at 60-70° C. to form a homogeneous solution; wherein the molar ratio of trehalose to anhydrous calcium chloride is 1:1.5-2.0, and the amount of the nanocellulose whisker framework added is 0.5-1.5% of the total mass of trehalose and anhydrous calcium chloride; S12, cooling the homogeneous solution of step S11 to -40 to -30°C at a rate of 5-10°C / min, keeping the temperature and freezing for 2-3 hours to obtain a frozen body; S13, placing the frozen body obtained in step S12 in a freeze dryer with a vacuum degree of ≤10 Pa, and subliming and dehydrating at -50 to -45°C for 24-36 hours to obtain a freeze-dried solid; S14. The freeze-dried solid obtained in step S13 is subjected to ball milling at a speed of 400-600 rpm for 20-30 minutes under an inert atmosphere, and sieved to obtain eutectic composite particles with a particle size of 10-50 μm.

[0036] In the above technical solution, the nanocellulose whisker framework refers to rod-shaped nanocrystals with a diameter of 5-20 nm and a length of 1-2 μm, modified with 3-aminopropyltriethoxysilane to impart surface amino groups. The eutectic complex refers to a molecular-scale composite crystal formed by trehalose and anhydrous calcium chloride at a specific molar ratio (1:1.5-2.0). A homogeneous solution refers to an isotropic colloid formed by fully dispersing nanocellulose in deionized water without a phase separation interface. A freeze-dried solid refers to a porous framework structure formed by freeze-dehydration that retains the eutectic molecular arrangement.

[0037] In this technical scheme, nanocellulose whiskers were dispersed in a pH 4.5 acetate buffer solution, and 3-aminopropyltriethoxysilane (mass ratio 1:0.2) was added. The solution was hydrolyzed and condensed at 60°C for 4 hours to obtain an aminated backbone. This backbone was then dissolved in deionized water with trehalose and anhydrous calcium chloride in appropriate proportions and stirred at 65°C to form a transparent, homogeneous solution. The solution was then cooled to -35°C at a rate of 7°C / min and frozen for 2.5 hours to form an ice crystal template. The frozen structure was then placed in a -48°C freeze dryer (vacuum ≤ 10 Pa) for 30 hours to allow sublimation and dehydration to obtain a porous freeze-dried structure. Finally, the structure was ball-milled at 500 rpm under argon for 25 minutes, and particles of 20-40 μm were collected by sieving.

[0038] Conventional eutectics are prepared using a direct mixing freezing method. Rapid freezing (>20°C / min) results in uneven ice crystal size (10-200μm), forcing calcium chloride into the interstitial spaces between the crystals, forming concentrated areas that trigger deliquescence and collapse. This method utilizes: the hydrogen-bonded network of the nanocellulose backbone (each whisker contains >100 -OH groups) to constrain the solute molecules for uniform distribution; programmed cooling to control the ice crystal growth rate to ≤1μm / min, forming a uniform ice crystal template with a diameter of 50-100nm; and deep freeze dehydration to prevent remelting and maintain the eutectic molecular orientation. Conventional ball milling in air introduces moisture, leading to localized deliquescence. This process fragments the freeze-dried body under an inert atmosphere, eliminating stress concentration points.

[0039] This technical solution yields a structurally stable mineralization accelerator: a nanocellulose skeleton forms a three-dimensional support network, resisting volume deformation caused by humidity fluctuations in concrete. A uniform mesoporous structure (pore size 20-50 nm) slows pore fluid permeation through capillary action. Trehalose-calcium chloride molecules form a stable coordination structure through hydrogen and ionic bonds, ensuring a linear release of calcium ions. The eutectic complex gradually dissociates in the alkaline environment of the crack (pH > 10). The released calcium ions synergize with microbial metabolites to form calcite nuclei, achieving gradient mineralization repair along the crack depth.

[0040] In another technical solution, the concrete anti-cracking self-repairing agent and the directional mineralization promoter are coated with a magnetically responsive shell, which includes an electrostatic adsorption layer, a magnetic carrier layer and an encapsulation layer from the inside to the outside; the electrostatic adsorption layer is a positively charged polyethyleneimine polymer with a thickness of 2-5nm; the magnetic carrier layer is amino-ferric oxide nanoparticles with a particle size of 10-20nm, which are fixed on the electrostatic adsorption layer by electrostatic action; the encapsulation layer is a hydrophobic silica vapor deposition film with a thickness of 3-8nm.

[0041] In the above technical solution, the magnetically responsive shell refers to a three-layer functional structure coating the surface of the eutectic composite particles: an electrostatic adsorption layer consisting of a positively charged polyethyleneimine (PEI) polymer film with a thickness of 2-5 nm; a magnetic carrier layer composed of 10-20 nm amined ferrosoferric oxide (Fe₃O₄-NH₂) nanoparticles fixed by electrostatic forces; and an encapsulation layer consisting of a hydrophobic silica vapor-deposited film with a thickness of 3-8 nm. Directed migration refers to the ability of the composite particles to accumulate in a target region under the influence of an external gradient magnetic field.

[0042] In this technical solution, the prepared eutectic composite particles were dispersed in a pH 5.5 citrate buffer, then a 0.5wt% PEI solution (molecular weight 25kDa) was added and stirred for 45 minutes to form an electrostatic adsorption layer. Free PEI was removed by centrifugation, and the particles were redispersed in the same buffer. Fe₃O₄-NH₂ nanoparticles were added at a 1:1 weight ratio, and ultrasonic treatment was performed at 35°C for 30 minutes to construct the magnetic carrier layer. The composite particles were then placed in a vapor deposition chamber, and hexamethyldisilazane vapor was introduced. The reaction was continued at 180°C and 0.3 Pa for 1.5 hours to form a uniform hydrophobic encapsulation layer.

[0043] Conventional magnetic modification technology uses a physical mixing method to simply blend magnetic particles with repair agents. The following failures occur in the high ionic strength (>0.5M) environment of concrete pore fluid: the magnetic particles agglomerate and precipitate due to the attenuation of the ζ potential (<-10mV); the hydrophilic surface of the unencapsulated particles adsorbs Ca(OH)2 crystals, blocking the magnetic response pathway.

[0044] This solution's three-layer structure achieves functional decoupling: the PEI layer maintains a positive surface charge through protonated amine groups (-NH⁺), counteracting ion shielding effects; the hydrophobic SiO₂ encapsulation layer blocks water permeation channels, preventing calcium hydroxide deposition. While conventional magnetic guidance systems experience a magnetic response intensity decay of over 50% after 28 days, this structure maintains a stable magnetic moment for 90 days.

[0045] This technical solution enables precise targeting of the mineralization accelerator: the electrostatic adsorption layer captures calcium ions within the crack region, forming localized enrichment points; the magnetic carrier layer generates a 42-45°C thermal effect in response to the alternating magnetic field, triggering the melting of the eutectic complex to release active components; and the hydrophobic encapsulation layer blocks pore fluid erosion, maintaining magnetic stability. Driven by the gradient magnetic field, the particles migrate to the crack tips, accelerating calcite deposition through a synergistic thermal-chemical effect, thus overcoming the distribution dilemma of traditional repair agents in microcracks, where they are concentrated at the edges and depleted in the center.

[0046] In another technical solution, the preparation method of the concrete anti-cracking self-repairing agent and the directional mineralization accelerator with a surface coated magnetic responsive shell is as follows: S21, dispersing the directional mineralization promoter particles in a buffer solution of pH 5.0-6.0, adding a positively charged polyethyleneimine polymer, and stirring the mixture for 30-60 minutes to form an electrostatic adsorption layer with a thickness of 2-5 nm; S22, adding amino-ferroferric oxide nanoparticles with a particle size of 10-20 nm to the system of step S21, and ultrasonically treating at 25-35° C. for 20-40 minutes to fix the magnetic particles to the surface of the electrostatic adsorption layer through electrostatic action to form a magnetic carrier layer, thereby obtaining composite particles; S23, the composite particles of step S22 are placed in a vapor deposition reaction chamber, and hexamethyldisilazane vapor is introduced, and reacted at 150-200℃ and 0.1-0.5Pa pressure for 1-2 hours to form a hydrophobic silica encapsulation layer with a thickness of 3-8nm.

[0047] In the above technical solution, the buffer system refers to a citric acid-disodium hydrogen phosphate solution with a pH of 5.0-6.0, and the ionic strength is 0.05-0.1M to maintain charge stability. The ultrasonic treatment parameters are constant temperature cavitation at a frequency of 40kHz and a power density of 0.5W / mL. The vapor deposition reaction refers to the process of cracking and deposition of hexamethyldisilazane (HMDS) in a low-pressure thermal environment to form an amorphous silica film.

[0048] In the technical solution, the composite particles are dispersed in a pH 5.8 buffer, 1.0wt% polyethyleneimine (PEI, molecular weight 10kDa) is added, and slow stirring at 50rpm is carried out for 40 minutes to form an electrostatic adsorption layer. Then, 2% by mass of amino-functionalized ferroferric oxide nanoparticles (particle size 15±3nm) are added dropwise, and placed in a 35℃ ultrasonic tank for treatment for 30 minutes, with the ultrasonic power density controlled at 0.5W / mL. The particles are collected by centrifugation and transferred to a vapor deposition chamber, HMDS vapor is introduced, the temperature is raised to 170℃ under a vacuum of 0.2Pa, and the reaction is maintained for 1 hour. After the reaction is completed, the temperature is replaced by nitrogen to room temperature.

[0049] Traditional magnetic carrier layer construction uses high-speed stirring method (>500rpm), which causes the magnetic particles to collide and agglomerate due to fluid shear force, forming >100nm agglomerates and blocking the carrier pores. The present solution achieves the following: the buffer solution has a pH of 5.8, which protonates the PEI to 90%, enhancing the electrostatic attraction; low-intensity ultrasound (0.5W / mL) generates micron-sized cavitation bubbles, uniformly dispersing the magnetic particles without damaging the adsorption layer. Conventional vapor deposition uses pulse heating (>50℃ / min), which forms >20nm thick films at the edges of the particles and <2nm on the flat surfaces; the linear heating (5℃ / min) of the present process combined with the low-pressure environment (0.2Pa) allows the HMDS cracking products to diffuse uniformly on the particle surface, forming a continuous encapsulation film with a thickness fluctuation of <±1nm.

[0050] In the above technical solution, the structural integrity of the magnetic response shell is ensured: the buffer system maintains the extended conformation of the PEI molecular chain, maximizing the adsorption site density; ultrasonic cavitation breaks through the van der Waals force barrier between magnetic particles, achieving single-particle dispersion; low-temperature vapor deposition avoids thermal decomposition of eutectic compounds, forming a dense hydrophobic barrier. The resulting particles remain monodispersed in the pore fluid of concrete, with a magnetic response strength decay rate reduced to less than 5% per month, meeting the precise magnetic guidance requirements during the service period. The encapsulation layer isolates water and oxygen permeation, maintaining the stability of the ferroferric oxide crystal form, and breaking through the technical bottleneck of irreversible decay of magnetic performance in traditional processes.

[0051] In another technical solution, the concrete anti-cracking self-repairing agent is provided with a gradient transition layer on the surface of the magnetothermal responsive capsule layer, which includes, from the inside to the outside, a first bonding layer, a second cross-linking layer and a third permeation layer; the first bonding layer is a polydopamine coating with a thickness of 5-10nm, which is coated on the surface of the magnetothermal responsive capsule layer; the second cross-linking layer is a copolymer network of polyethylene glycol diacrylate and zinc acrylate, with a network pore diameter of 30-50nm; the third permeation layer is a cage-type polysilsesquioxane nanoparticle with a surface modified epoxy group, with a particle size of 20-40nm, which is dispersed in the second cross-linking layer network.

[0052] In the above technical solution, the gradient transition layer refers to a three-level functional interface between the magnetothermally responsive capsule layer and the pH-sensitive hydrogel coated on the Fe3O4@SiO2 core-shell nanoparticles: the first binding layer is a polydopamine coating, which chelates to the magnetic particle surface through catechol groups; the second crosslinking layer is a free radical copolymerization network of polyethylene glycol diacrylate (PEGDA) and zinc acrylate (ZnAA); and the third permeation layer is epoxy-modified caged polysilsesquioxane (POSS) nanoparticles, embedded in the crosslinking network through a ring-opening reaction. Interlayer stress buffering refers to the absorption of thermal expansion differences through chemical bonding and mechanical interlocking.

[0053] In this technical solution, the prepared magnetothermal responsive capsule layer was immersed in 2mg / mL dopamine hydrochloride in Tris buffer (pH 8.8) and allowed to stand for 1.5 hours under nitrogen protection to form a 5-8nm polydopamine layer. It was then transferred to a prepolymer solution containing 15wt% PEGDA (molecular weight 400Da) and 5wt% ZnAA, and then placed under 12mW / cm 2 The film was irradiated under UV light for 8 minutes to initiate polymerization. Finally, 2 wt% epoxy-group POSS nanoparticles (particle size 30 ± 5 nm) were added and irradiated for another 2.5 minutes to open the epoxy group bonding network and form a gradient transition layer.

[0054] Traditional interface treatment uses a single coupling agent (such as silane KH550), whose monolayer thickness is less than 2nm and the functional group density is low. In the magnetothermal cycle (ΔT>20℃), due to the mismatch of expansion coefficient (magnetic capsule α≈10×10⁻ 6 / K, hydrogel α≈200×10⁻ 6 / K) to trigger interlayer peeling. This scheme achieves strong chelation (Fe-O bond energy > 250kJ / mol) by: converting the catechol / quinone structure of polydopamine; Zn in the PEGDA-ZnAA copolymer network 2+The structure forms coordination bonds (bond energy 120-150 kJ / mol) with the carboxyl groups of the hydrogel, reversibly breaking to absorb deformation energy. POSS nanoparticles (rigidity >20 GPa) act as network reinforcements, with surface epoxy groups opening to form covalent crosslinks. Compared to the interfacial peel force of conventional processes (<0.5 N / m), this structure achieves an improved peel strength of >5 N / m.

[0055] The above technical solution achieves reliable functional integration between layers: the polydopamine layer eliminates the surface energy barrier of the magnetic capsule through metal coordination bonds; the cross-linked network's hydrophilic-hydrophobic balance is designed to match the hydrogel's swelling behavior; and the 30-50 nm through-channels constructed by the POSS particles provide directionally guided migration of repair components. The gradient structure simultaneously transmits the magnetothermal effect to deeper areas, increasing the temperature uniformity deep within the crack to over 90%, preventing local overheating that could damage microbial activity. Ultimately, a complete interfacial pathway is formed, from energy transfer to material transport, breaking through the technical bottleneck of interlayer failure in the composite repair system.

[0056] In the above technical solution, the polydopamine coating (5-10nm) forms a strong chelation effect with the Fe3O4@SiO2 surface through the catechol group to enhance the interfacial binding energy; the Zn in the zinc acrylate cross-linked network 2+ It coordinates with the carboxyl group of the hydrogel to buffer the difference in expansion stress; the epoxy groups of the caged polysilsesquioxane nanoparticles (20-40nm) react with the cross-linked network to form 30-50nm through-pores to promote deep penetration.

[0057] The present invention also provides a method for preparing a concrete anti-cracking self-repairing agent, which comprises the following steps: Step 1: Disperse Bacillus pasteurianus spores in phosphate buffer, add ZSM-5 zeolite molecular sieve, and oscillate and infiltrate at a vacuum degree of 0.08-0.1 MPa and a temperature of 25-30°C for 30-60 minutes to obtain a microbial remediation unit; Step 2: mixing Fe3O4@SiO2 core-shell nanoparticles with a precursor solution containing 2-hydroxyethyl acrylate, glycidyl methacrylate, and photoinitiator Irgacure 2959 to obtain a mixture; Step 3: Apply the mixture obtained in step 2 to the surface of the microbial remediation unit obtained in step 1 to form a coating system, and perform the following treatments on the coating system in sequence: S31, adding 0.5-1% by mass of dopamine hydrochloride to the coating system, and standing at pH 8.5-9.0 for 1-2 hours under nitrogen protection to form a first polydopamine binding layer; S32, adding polyethylene glycol diacrylate with a molecular weight of 200-400Da and zinc acrylate in a molar ratio of 3:1, under the UV intensity of 10-15mW / cm 2Irradiate for 5-10 minutes to initiate free radical polymerization to form a second cross-linked layer; S33, finally adding 2-5% of the mixture by mass of surface-modified epoxy group-containing cage-type polysilsesquioxane nanoparticles, and continuing irradiation for 2-3 minutes to form a third permeation layer and a magnetothermal responsive capsule layer; Step 4: adding the mesoporous silica particles, PLGA microspheres, and directional mineralization promoter to the product of step 3, and mixing at a shear rate of 200-400 rpm and a temperature of 15-20° C. for 20-30 minutes to obtain a composite; Step 5: Place the compound obtained in step 4 in a mold, and allow it to stand and cure for 48-72 hours in an environment with a humidity of ≥90% and a temperature of 35-40° C. to obtain a concrete anti-cracking self-repairing agent.

[0058] In the above technical solution, vacuum infiltration refers to the physical process of driving spores into the zeolite pores under a negative pressure of 0.08-0.1 MPa, with the buffer osmotic pressure maintaining pressure equilibrium inside and outside the cells. Photopolymerization refers to the UV-induced free radical cross-linking reaction of acrylate monomers, with the irradiation intensity controlling the heat release rate. The gradient transition layer construction sequence strictly follows the irreversible reaction sequence of "polydopamine binding layer → cross-linked network layer → permeable particle layer."

[0059] In this technical solution, Bacillus pasteurianus spores were suspended in an isotonic phosphate buffer (osmotic pressure 300 mOsm / L), then added to ZSM-5 zeolite molecular sieves and placed in a vacuum chamber for oscillation at 0.09 MPa and 28°C for 45 minutes. Fe₃O₄@SiO₂ core-shell particles were mixed with a photosensitive prepolymer containing 2-hydroxyethyl acrylate, glycidyl methacrylate, and 0.5 wt% Irgacure 2959 and coated on the zeolite surface. The coating system was carried out in the following order: 0.8wt% dopamine hydrochloride was added, pH 8.8 nitrogen environment was allowed to stand for 1.2 hours to form a bonding layer; immersion in a solution containing PEGDA and zinc acrylate (molar ratio 3:1), 12mW / cm² UV irradiation for 7 minutes to build a cross-linked network; 3wt% epoxy POSS nanoparticles were incorporated and irradiation was continued for 2 minutes to complete the bonding of the permeation layer; finally, PLGA microspheres and directional mineralization promoter were added, mixed at a shear rate of 350rpm and 18℃ for 25 minutes, and cured at 90% humidity and 38℃ for 60 hours.

[0060] The conventional spore loading method uses a normal pressure immersion method. The air resistance effect in the zeolite pores causes the spores to only adhere to the surface at a depth of 5μm. After concrete mixing, >70% of the spores fall off. The 0.09MPa vacuum degree of this solution allows the buffer solution to fully fill the pores, eliminating the air-liquid interfacial tension and increasing the spore penetration depth to more than 20μm. Conventional photopolymerization uses >50mW / cm 2High-intensity ultraviolet radiation, local temperature> 60℃, denatures and inactivates spore proteins; this process controls the radiation intensity to ≤ 15mW / cm 2 The process was carried out in stages, with the system temperature maintained below 35°C. While the existing simultaneous gradient layer construction method triggers competitive reactions among the components, with the cross-linked network enveloping the POSS particles and resulting in pore blockage, this sequential construction ensures sufficient interfacial reaction between the layers: polydopamine completes chelation, then forms a cross-linked network, and finally introduces the POSS ring-opening bond.

[0061] This technical solution achieves non-destructive construction of functional structures: vacuum penetration pressure matches the spore cell wall strength threshold to prevent cell rupture; staged photopolymerization limits the exothermic peak by controlling the energy dose, ensuring microbial activity; and a gradient transition layer sequentially reacts to form a three-level bonding interface of "chelation-crosslinking-anchoring," increasing the interlayer bonding energy to over five times that of traditional processes. The resulting composite repair agent exhibits >95% bioactivity retention. Its magnetothermal responsiveness and pH sensitivity form a synergistic mechanism with microbial activity, meeting the requirements for long-term self-repair of concrete cracks.

[0062] <Example 1> A concrete anti-cracking self-repairing agent comprises the following raw materials in parts by weight: 100 parts ZSM-5 zeolite molecular sieve (the molar ratio of SiO2 to Al2O3 in the ZSM-5 zeolite molecular sieve is 40:1, and the pore size is 0.85 nm), 6 parts Bacillus pasteurianus spores, 12 parts mesoporous silica particles loaded with 150 nm calcium L-aspartate, 12 parts Fe3O4@SiO2 core-shell nanoparticles, 10 parts PLGA microspheres, and 4 parts of a directional mineralization accelerator. The PLGA microspheres contain yeast extract; the directional mineralization accelerator is a eutectic complex formed by trehalose and anhydrous calcium chloride at a mass ratio of 1:1.8.

[0063] A method for preparing a concrete anti-cracking self-repairing agent comprises the following steps: Step 1: Disperse Bacillus pasteurianus spores in 0.1M phosphate buffer (pH=7.4), add ZSM-5 zeolite molecular sieve, shake and infiltrate at a vacuum degree of 0.09MPa and a temperature of 28°C for 45 minutes, centrifuge and freeze-dry to obtain a microbial remediation unit; Step 2: Fe3O4@SiO2 core-shell nanoparticles are mixed with a precursor solution containing 2-hydroxyethyl acrylate, glycidyl methacrylate, and photoinitiator Irgacure 2959 (15 parts of 2-hydroxyethyl acrylate, 10 parts of glycidyl methacrylate, and 0.25 parts of photoinitiator Irgacure 2959), and ultrasonically dispersed for 10 minutes to obtain a mixture; Step 3: Apply the mixture obtained in step 2 to the surface of the microbial remediation unit obtained in step 1 to form a coating system, and perform the following treatments on the coating system in sequence: S31, adding 0.8% by mass of dopamine hydrochloride to the coating system, and standing at pH 8.8 for 1.5 hours under nitrogen protection to form a first polydopamine binding layer; S32, then add polyethylene glycol diacrylate with a molecular weight of 300Da and zinc acrylate in a molar ratio of 3:1, and 2 Irradiation for 8 minutes to initiate free radical polymerization to form a second cross-linked layer; S33, finally, adding 3% of the mixture by mass of surface-modified epoxy group-containing cage-type polysilsesquioxane nanoparticles, and continuing irradiation for 2.5 minutes to form a third permeation layer and a magnetothermal responsive capsule layer; Step 4: adding PLGA microspheres and a directional mineralization promoter to the product of step 3, and mixing at a shear rate of 300 rpm and a temperature of 15-20° C. for 25 minutes to obtain a composite; Step 5: Place the compound obtained in step 4 in a mold, and allow it to stand and cure for 60 hours in an environment with a humidity of ≥90% and a temperature of 38° C. to obtain a concrete anti-cracking self-repairing agent.

[0064] <Example 2> A concrete anti-cracking self-repairing agent and a preparation method thereof, which differs from Example 1 in that polyethyleneimine is bonded to the surface of the mesoporous silica particle carrier, and poly-γ-glutamic acid is adsorbed by electrostatic action to form a double-layer slow-release barrier coated with calcium L-aspartate, specifically: 10 g of mesoporous SiO2 particles (pore size 4 nm, particle size 150 nm) were dispersed in 200 mL of anhydrous ethanol; 2 g of 3-aminopropyltriethoxysilane (APTES) was added and refluxed at 70°C for 4 hours; the mixture was centrifuged and washed (8000 rpm × 10 min) and dried in a vacuum at 80°C to obtain aminated mesoporous SiO2. The aminated mesoporous SiO2 was immersed in 50 mL of 10 wt% L-aspartic acid calcium solution; vacuum infiltration (0.09 MPa, 25 ° C × 2 h) was performed; the mixture was filtered and dried at 40 ° C to obtain calcium-loaded particles; The calcium-loaded particles were dispersed in a pH 9.0 boric acid buffer (0.1 M). 0.5 g of polyethyleneimine (PEI, Mn = 25 kDa) was added and stirred at 200 rpm for 30 min. Free PEI was removed by centrifugation to obtain PEI-modified particles. The PEI-modified particles were transferred to a pH 5.0 sodium acetate buffer (0.1 M); 1 g of poly-γ-glutamic acid (PGA, Mw=200 kDa) was added and stirred at 100 rpm for 1 h; and freeze-dried to obtain double-layer barrier calcium-loaded particles.

[0065] The rest of the conditions and parameters are the same as in Example 1.

[0066] <Example 3> A concrete anti-cracking self-repairing agent and a preparation method thereof, which are different from Example 1 in that carbon nanotubes are arranged in the nanochannels of the ZSM-5 type zeolite molecular sieve loaded with Bacillus pasteurii spores, the carbon nanotubes are carboxylated single-walled carbon nanotubes, the diameter is 1.5 nm, the length is 300 nm, and the surface grafting density is 3-5 per 100 nm 2 ; the carbon nanotube network accounts for 12% of the volume of the zeolite channel, and the two ends are connected to the surface of the spores and the inner wall of the zeolite pore, respectively.

[0067] The specific operation is as follows: Take single-walled carbon nanotubes (diameter 1.5 nm, length 300 nm) 1 g; treat with mixed acid (H2SO4:HNO3=3:1), ultrasonic oxidation at 60°C for 6 h; dialysis to pH 6.0 to obtain carboxylated carbon tubes (-COOH density 4 per 100 nm 2 ); Immerse ZSM-5 zeolite (SiO2 / Al2O3=40:1) in a PBS solution containing 1 wt% carboxylated carbon tubes; add 0.1 M EDC / NHS activator (EDC:NHS=5:2 molar ratio); oscillate at 40°C for 4 h to condense the carbon tubes with the silanol groups of the zeolite; Disperse Bacillus pasteurii spores (1×10 9 CFU / g) in 0.1 M MES buffer (pH 6.0); add the carbon tube modified zeolite, vacuum infiltrate at 0.09 MPa for 45 min; in-situ amidation of the amino groups of the spore coat protein and the carboxyl groups of the carbon tubes.

[0068] The rest of the conditions and parameters are the same as in Example 1.

[0069] <Example 4> A concrete anti-cracking self-repairing agent and a preparation method thereof, which are different from Example 1 in that the preparation method of the directional mineralization promoter is as follows: S11, take nanocellulose whiskers (diameter 15 nm, length 1.2 μm) 0.1 g, add 1 g of APTES (silane coupling agent KH550 (APTES) chemical name γ-aminopropyl triethoxysilane) / ethanol solution (10 wt%), react at 60°C for 6 h; centrifugal washing to obtain an amine group modified whisker skeleton (a nanocellulose whisker skeleton body modified with 3-aminopropyl triethoxysilane on the surface) S12, dissolving the aminated whisker skeleton, 20 g of trehalose and 30 g of anhydrous calcium chloride in deionized water, and stirring at 65° C. to form a homogeneous solution; the molar ratio of trehalose to anhydrous calcium chloride is 1:1.8, and the amount of the nanocellulose whisker skeleton added is 1% of the total mass of trehalose and anhydrous calcium chloride; S13, cooling the homogeneous solution of step S12 to -35°C at a rate of 7°C / min, keeping the temperature and freezing for 2.5 hours to obtain a frozen body; S14, placing the frozen body obtained in step S13 in a freeze dryer with a vacuum degree of ≤10 Pa, and sublimating and dehydrating at -48°C for 30 hours to obtain a freeze-dried solid; S15. The freeze-dried solid obtained in step S14 is subjected to ball milling at a speed of 500 rpm for 25 minutes under an inert atmosphere, and sieved to obtain eutectic complex particles with a particle size of 20-40 μm, thereby obtaining an orientation promoter.

[0070] Furthermore, the surface of the directional mineralization promoter is coated with a magnetically responsive shell, specifically: S21, taking the directional accelerator prepared above, dispersing it in a pH 5.8 citrate buffer (0.05 M); adding 0.5 g of PEI (polyethyleneimine polymer) (Mn=10 kDa), stirring at 300 rpm for 40 minutes; centrifuging to remove free PEI, and obtaining PEI electrostatic adsorption layer particles; S22, redispersing the PEI electrostatic adsorption layer particles in a pH 5.8 citrate buffer (0.05 M), adding 15 nm amino-containing ferrosoferric oxide nanoparticles thereto, and ultrasonically treating at 35° C. for 30 minutes to fix the magnetic particles on the surface of the electrostatic adsorption layer by electrostatic action, forming a magnetic carrier layer, and obtaining composite particles; S23, placing the composite particles in step S22 in a vapor deposition reaction chamber, introducing hexamethyldisilazane vapor, and reacting at 180° C. and 0.3 Pa pressure for 1.5 hours to form a hydrophobic silica encapsulation layer with a thickness of 5.0±0.8 nm.

[0071] The remaining conditions and parameters are the same as in Example 1.

[0072] Comparative Example 1 A concrete anti-cracking self-repairing agent and a preparation method thereof, which differs from Example 1 in that a diatomaceous earth carrier is used instead of the ZSM-5 zeolite molecular sieve; the remaining conditions and parameters are the same as those in Example 1.

[0073] Comparative Example 2 A concrete anti-cracking self-repairing agent and a preparation method thereof, which differs from Example 1 in that calcium lactate is directly added instead of mesoporous silica-loaded calcium L-aspartate; the remaining conditions and parameters are the same as Example 1.

[0074] Comparative Example 3 A concrete anti-cracking self-repairing agent and a preparation method thereof, which differs from Example 1 in that S31, S32, and S33 are omitted, that is, the Fe3O4@SiO2 magnetothermal response capsule layer and the gradient transition layer are omitted, and the remaining conditions and parameters are the same as Example 1.

[0075] Comparative Example 4 A concrete anti-cracking self-repairing agent and a preparation method thereof, which differs from Example 1 in that a directional mineralization promoter is omitted, and other conditions and parameters are the same as Example 1.

[0076] <Test Example> The self-repairing agents obtained in Examples 1 to 4 and Comparative Examples 1 to 4 were tested as follows. The test results are shown in Table 1: 1. Spore survival rate: The specimens were immersed in simulated pore fluid (pH=13.2, Ca(OH)2 saturated solution). After 28 days, the repair agent was taken out to test the percentage of germinated spores (GB / T 4789.2). 2. Calcium utilization rate: After concrete mixing, collect pore fluid by centrifugation and measure free calcium ions by EDTA titration; effective calcium retention rate = (measured calcium content / theoretical addition amount) × 100%; 3. Repair efficiency: Crack width: Prefabricate a 0.15mm wide crack and measure the closing time; 4. Compressive strength recovery rate: The ratio of the compressive strength of the prefabricated cracked specimen (28-day curing) to that of the intact specimen 28 days after repair (GB / T 50081).

[0077] 5. Mineralization products: scrape sediments from the fracture area, dissolve them in hydrochloric acid, measure the amount of CO2 released, and convert it into CaCO3 mass (g / m 2 ) 6. Magnetothermal response effect: An infrared thermal imager monitors the local temperature changes of the cracks under an alternating magnetic field (20kHz, 300Gs, single action time 10 minutes, 3 cycles per day).

[0078] Table 1 Test results Group Spore survival rate (%) Calcium utilization rate (%) 0.15mm crack closure time (days) Compressive strength recovery rate (%) <![CDATA[矿化产物量 (g / m 2 )]]> Magnetothermal local temperature rise (℃) Example 1 92.5 ± 1.8 85.2 ± 2.1 5.0 ± 0.5 95.3 ± 1.2 38.7 ± 1.5 42.5 ± 0.8 Example 2 94.1 ± 1.5 86.7 ± 1.9 4.8 ± 0.3 96.0 ± 0.9 40.2 ± 1.8 43.0 ± 0.6 Example 3 96.3 ± 1.2 88.5 ± 1.7 4.2 ± 0.4 97.5 ± 0.7 43.1 ± 1.6 43.5 ± 0.5 Example 4 95.8 ± 1.4 87.3 ± 2.0 4.5 ± 0.3 96.8 ± 1.0 41.5 ± 1.7 44.5 ± 0.7 Comparative Example 1 3.2 ± 1.1 81.5 ± 2.8 14.3 ± 1.2 70.2 ± 2.5 12.5 ± 1.1 44.0 ± 1.0 Comparative Example 2 89.7 ± 2.0 34.8 ± 3.5 9.2 ± 0.8 75.6 ± 2.1 25.8 ± 1.3 43.8 ± 0.9 Comparative Example 3 90.5 ± 1.7 83.1 ± 2.3 21.5 ± 1.5 65.3 ± 2.8 10.7 ± 0.9 — Comparative Example 4 92.1±1.6 84.3±2.0 5.5±0.6 82.3±1.8 18.9±1.2 42.8±0.8 Note: All data are mean ± standard deviation of three replicate tests, consistent with the "7+7d / 28+28d compressive strength" test logic in CN110255948B, with the addition of a new indicator specifically for microbial remediation. The amount of mineralized product was verified by SEM-EDS analysis of the fracture area. In Examples 1-4, calcite deposited directionally along the fracture walls, while in Comparative Example 2, the sediment was dispersed within the matrix.

[0079] Through analysis of the data in Table 1, the technical solution of the present invention has significant advantages in the self-repair performance of concrete cracks: The spore survival rate of Examples 1-4 (92.5%~96.3%) was significantly higher than that of Comparative Example 1 (diatomaceous earth carrier, 3.2%), verifying the alkaline barrier effect of the ZSM-5 zeolite nanochannel; the calcium utilization rate (85.2%~88.5%) far exceeded that of Comparative Example 2 (direct addition of calcium lactate, 34.8%), reflecting the enzyme response slow release mechanism to avoid early calcium precipitation; the crack closure time (4.2~5.0 days) was shortened by 76% compared with Comparative Example 3 (without magnetothermal layer, 21.5 days), confirming that the magnetothermal response layer accelerated spore germination and component penetration by local heating (42.5~44.5℃); the amount of mineralized product (18.9~21.5 days) of Comparative Example 4 (without eutectic complex) was significantly higher than that of Comparative Example 2 (without eutectic complex). The eutectic complex's mass (g / m²) decreased by 51.2% compared to Example 1, and the compressive strength recovery rate decreased by 13.0%. This confirms the importance of directional mineralization for the eutectic complex. By lowering the crystallization energy barrier and providing spatial orientation, it promotes calcite deposition along the crack walls, achieving structural repair. This indicates that the directional mineralization of the eutectic complex and the gradient transition layer synergistically ensure the integrity of the structural repair. This demonstrates that the complementary functions of the components of the present invention form a synergistic "recognition-activation-mineralization" mechanism, overcoming the bottlenecks of spore inactivation, calcium source depletion, and delayed repair in traditional technologies.

[0080] The number of devices and processing scales described herein are intended to simplify the description of the present invention. Applications, modifications, and variations of the present invention will be readily apparent to those skilled in the art.

[0081] Although the embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the description and implementation methods. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.

Claims

1. A concrete anti-cracking self-repairing agent, characterized in that: The method comprises the following raw materials in parts by weight: 100 parts of ZSM-5 zeolite molecular sieve, 5-8 parts of Bacillus pasteurianus spores, 10-15 parts of mesoporous silica particles loaded with calcium L-aspartate having a particle size of 100-200 nm, 10-15 parts of Fe3O4@SiO2 core-shell nanoparticles, 8-12 parts of PLGA microspheres, and 3-5 parts of a directional mineralization promoter; Among them, Bacillus pasteurianus spores are loaded in the nanochannels of ZSM-5 zeolite molecular sieve to form a microbial remediation unit. The molar ratio of SiO2 and Al2O3 of ZSM-5 zeolite molecular sieve is 30-50:1, and the pore size is ≥0.8nm; Fe3O4@SiO2 core-shell nanoparticles are fixed by in-situ polymerization coating to form a magnetothermal responsive capsule layer coated on the surface of the microbial remediation unit; the particle size of Fe3O4@SiO2 core-shell nanoparticles is 50-100nm, and the shell thickness is 5-10nm; The PLGA microspheres contain yeast extract, and the PLGA microspheres are located at the interface between the zeolite carrier and the coating layer; The directional mineralization promoter is a eutectic complex formed by trehalose and anhydrous calcium chloride.

2. The concrete anti-cracking self-repairing agent according to claim 1, characterized in that: The surface of the mesoporous silica particle carrier is bonded with polyethyleneimine, and poly-γ-glutamic acid is adsorbed through electrostatic interaction to form a double-layer sustained-release barrier coated with L-aspartate calcium.

3. The concrete anti-cracking self-repairing agent according to claim 1, characterized in that: The nanochannels of the ZSM-5 zeolite molecular sieve loaded with Bacillus pasteurianus spores are provided with a carbon nanotube network; The carbon nanotubes are carboxylated single-walled carbon nanotubes with a diameter of 1-2nm, a length of 200-500nm, and a surface grafting density of 3-5 per 100nm. 2 The carbon nanotube network occupies 10-15% of the volume of the zeolite channel, and its two ends connect the spore surface to the inner wall of the zeolite channel.

4. The concrete anti-cracking self-repairing agent according to claim 1, characterized in that: The preparation method of the directional mineralization accelerator is specifically as follows: S11, dissolving a nanocellulose whisker framework whose surface is modified with 3-aminopropyltriethoxysilane, trehalose, and anhydrous calcium chloride in deionized water, and stirring at 60-70° C. to form a homogeneous solution; wherein the molar ratio of trehalose to anhydrous calcium chloride is 1:1.5-2.0, and the amount of the nanocellulose whisker framework added is 0.5-1.5% of the total mass of trehalose and anhydrous calcium chloride; S12, cooling the homogeneous solution of step S11 to -40 to -30°C at a rate of 5-10°C / min, keeping the temperature and freezing for 2-3 hours to obtain a frozen body; S13, placing the frozen body obtained in step S12 in a freeze dryer with a vacuum degree of ≤10 Pa, and subliming and dehydrating at -50 to -45°C for 24-36 hours to obtain a freeze-dried solid; S14. The freeze-dried solid obtained in step S13 is subjected to ball milling at a speed of 400-600 rpm for 20-30 minutes under an inert atmosphere, and sieved to obtain eutectic composite particles with a particle size of 10-50 μm.

5. The concrete anti-cracking self-repairing agent according to claim 4, characterized in that: The surface of the directional mineralization promoter is coated with a magnetically responsive shell, which includes an electrostatic adsorption layer, a magnetic carrier layer and an encapsulation layer from the inside to the outside; the electrostatic adsorption layer is a positively charged polyethyleneimine polymer with a thickness of 2-5nm; the magnetic carrier layer is amino-containing ferrosoferric oxide nanoparticles with a particle size of 10-20nm, which are fixed on the electrostatic adsorption layer by electrostatic action; the encapsulation layer is a hydrophobic silica vapor deposition film with a thickness of 3-8nm.

6. The concrete anti-cracking self-repairing agent according to claim 5, characterized in that: The preparation method of the magnetically responsive shell coated on the surface of the directional mineralization promoter is specifically as follows: S21, dispersing the directional mineralization promoter particles in a buffer solution of pH 5.0-6.0, adding a positively charged polyethyleneimine polymer, and stirring the mixture for 30-60 minutes to form an electrostatic adsorption layer with a thickness of 2-5 nm; S22, adding amino-ferroferric oxide nanoparticles with a particle size of 10-20 nm to the system of step S21, and ultrasonically treating at 25-35° C. for 20-40 minutes to fix the magnetic particles to the surface of the electrostatic adsorption layer through electrostatic action to form a magnetic carrier layer, thereby obtaining composite particles; S23, placing the composite particles in step S22 in a vapor deposition reaction chamber, introducing hexamethyldisilazane vapor, and reacting at 150-200° C. and 0.1-0.5 Pa pressure for 1-2 hours to form a hydrophobic silicon dioxide encapsulation layer with a thickness of 3-8 nm.

7. The concrete anti-cracking self-repairing agent according to claim 1, characterized in that: A gradient transition layer is provided on the surface of the magnetothermal responsive capsule layer, which includes, from the inside to the outside, a first binding layer, a second cross-linking layer and a third permeation layer; the first binding layer is a polydopamine coating with a thickness of 5-10 nm, which is coated on the surface of the magnetothermal responsive capsule layer; the second cross-linking layer is a copolymer network of polyethylene glycol diacrylate and zinc acrylate, with a network pore diameter of 30-50 nm; the third permeation layer is a cage-type polysilsesquioxane nanoparticle with a surface modified epoxy group, with a particle size of 20-40 nm, which is dispersed in the second cross-linking layer network.

8. A method for preparing a concrete anti-cracking self-repairing agent, characterized in that: The following steps are involved: Step 1: Disperse Bacillus pasteurianus spores in phosphate buffer, add ZSM-5 zeolite molecular sieve, and oscillate and infiltrate at a vacuum degree of 0.08-0.1 MPa and a temperature of 25-30°C for 30-60 minutes to obtain a microbial remediation unit; Step 2: mixing Fe3O4@SiO2 core-shell nanoparticles with a precursor solution containing 2-hydroxyethyl acrylate, glycidyl methacrylate, and photoinitiator Irgacure 2959 to obtain a mixture; Step 3: Apply the mixture obtained in step 2 to the surface of the microbial remediation unit obtained in step 1 to form a coating system, and perform the following treatments on the coating system in sequence: S31, adding 0.5-1% by mass of dopamine hydrochloride to the coating system, and standing at pH 8.5-9.0 for 1-2 hours under nitrogen protection to form a first polydopamine binding layer; S32, adding polyethylene glycol diacrylate with a molecular weight of 200-400Da and zinc acrylate in a molar ratio of 3:1, under the UV intensity of 10-15mW / cm 2 Irradiate for 5-10 minutes to initiate free radical polymerization to form a second cross-linked layer; S33, finally adding 2-5% of the mixture by mass of surface-modified epoxy group-containing cage-type polysilsesquioxane nanoparticles, and continuing irradiation for 2-3 minutes to form a third permeation layer and a magnetothermal responsive capsule layer; Step 4: adding the mesoporous silica particles, PLGA microspheres, and directional mineralization promoter to the product of step 3, and mixing at a shear rate of 200-400 rpm and a temperature of 15-20° C. for 20-30 minutes to obtain a composite; Step 5: Place the compound obtained in step 4 in a mold, and allow it to stand and cure for 48-72 hours in an environment with a humidity of ≥90% and a temperature of 35-40° C. to obtain a concrete anti-cracking self-repairing agent.

Citation Information

Patent Citations

  • Concrete crack-resistant self-healing agent and its preparation method and crack-resistant self-healing concrete

    CN110255948B

Cited By

  • Preparation method of modified zeolite, functional concrete and preparation method of functional concrete

    CN121342389A

  • Low-crack high-corrosion-resistance concrete for wind power tower drum and preparation method of low-crack high-corrosion-resistance concrete

    CN121627357A

  • Low-crack high-corrosion-resistant concrete for wind power tower and preparation method thereof

    CN121627357B